PENGARUH APLIKASI BERBASIS ANDROID AYO DEDIS UNTUK PENINGKATAN PENGETAHUAN GIZI SEIMBANG TERHADAP STUNTING PADA IBU HAMIL - LENA SEKARWATI (Media Husada Journal Of Nursing Science, 2022)
Abstrak Sekarwati, Lena. 2021. The Effect of Android-Based Ayo Dedis Application on Increasing Knowledge of Balanced Nutrition on Stunting in Pregnant Women During a Pandemic in the Work Area of Karangploso Health Center, Malang Regency. Thesis. Nursing Study Program of Widyagama Husada School of Health. Advisors: (1) Frengki Apryanto, S.Kep., Ners., M.Kep. (2) Rosly Zunaedi, S.Kep., Ners., M.Kep. Background: Stunting may occur in mother who are too young, too old, having many birth record and short birth interval. Today is an era where everyone uses social media to interact and find information. Therefore researchers are interested in conducting research using android-based applications for prevention and early detection of pregnant women in order to reduce stunting rates and get enough information with gadgets. Objective: to examine the effect of the Android-based Ayo Dedis application on pregnant women. Methods: The effect of pregnant women's knowledge about stunting before and after using the "Ayo Dedis" application was tested using the Paired T-Test which is a parametric test that can be used on two paired data. The purpose of this test is to see whether there is a difference in the mean between two paired or related samples, whether there is a significant relationship or difference in the study used with ordinal data. Results: Based on data analysis, the paired sample test is an output table that shows the results of the tests carried out. This can be seen from the significance value (2-tailed) of 0.004 (p<0.05). So that the results of the pretest and posttest experienced a significant change. Based on descriptive statistics, pretest and posttest proved to be higher than posttest. Conclusion: It can be concluded that there is effect of the android-based Ayo Dedis application on increasing knowledge of balanced nutrition in pregnant women before and after giving the application with results (p <0.05). Literature : 32 References (2010-2021) Keywords: Stunting, Application, Pregnant Women